Mutual domestication - Siles, Ignacio (2024)
This trailer develops the notion of mutual domestication between people and algorithms as an analytical key to understand algorithmic cultures. It is argued that this idea offers opportunities to rethink the relationship between people and technologies in the era of algorithms and artificial intelligence. The importance of conceptualizing agency as a cyclical, fluid process full of friction is highlighted. This trailer suggests that the perspective of “mutual domestication” opens new avenues of research, particularly concerning time and understudied dynamics within Latin American contexts. Thus, this notion seeks to deepen our understanding of the specific realities of the Global South in the experience of digital media.